Facilitating and Regulating Commerce: Commentary - Frankel, Susy (Victoria University of Wellington Law Review, 2002)
This paper was written as commentary for the Facilitating and Regulating Commerce seminar session. The author discusses the regulation of commerce in New Zealand through the competition law mechanisms of the Commerce Act 1986 and intellectual property law. The paper then notes the term "commercial dispute" is difficult to define, and challenges the idea of needing specialist commercial judges in New Zealand where the commercial market is relatively small. In the absence of empirical evidence that a lack of regulation has harmed New Zealand's economic interests, the author concludes that it is worth waiting to see whether such sweeping legal changes are required.